2009
DOI: 10.1042/bj20080921
|View full text |Cite
|
Sign up to set email alerts
|

A novel motif at the C-terminus of palmitoyltransferases is essential for Swf1 and Pfa3 function in vivo

Abstract: S-acylation (commonly known as palmitoylation) is a widespread post-translational modification that consists of the addition of a lipid molecule to cysteine residues of a protein through a thioester bond. This modification is predominantly mediated by a family of proteins referred to as PATs (palmitoyltransferases). Most PATs are polytopic membrane proteins, with four to six transmembrane domains, a conserved DHHC motif and variable C-and N-terminal regions, that are probably responsible for conferring localiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
36
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 45 publications
1
36
0
Order By: Relevance
“…Although PATs of a given species can localize at diverse membrane compartments (Ohno et al, 2006;Greaves and Chamberlain, 2011;Batistic, 2012), little is known about the targeting determinants. Mutation at a palmitoyltransferase conserved C terminus (PaCCT) motif of yeast Pfa3 resulted in its functional loss and mistargeting to the vacuolar lumen (González Montoro et al, 2009). However, the PaCCT motif is not present in Arabidopsis PAT10.…”
Section: Subcellular Targeting Of Pat10mentioning
confidence: 99%
“…Although PATs of a given species can localize at diverse membrane compartments (Ohno et al, 2006;Greaves and Chamberlain, 2011;Batistic, 2012), little is known about the targeting determinants. Mutation at a palmitoyltransferase conserved C terminus (PaCCT) motif of yeast Pfa3 resulted in its functional loss and mistargeting to the vacuolar lumen (González Montoro et al, 2009). However, the PaCCT motif is not present in Arabidopsis PAT10.…”
Section: Subcellular Targeting Of Pat10mentioning
confidence: 99%
“…A recent study on the yeast PAT Akr1 has indicated that the protein can still be acylated in trans when this cysteine is mutated, indicating that other sites for S-acylation are possible (23). Moreover, a recent proteomics study has shown that the human DHHCs 5, 6, and 8 are autoacylated outside of the DHHC-CRD in three cysteines located in the C-terminal region in a CCX [7][8][9][10][11][12][13] C(S/T) motif (24). However, this motif is not present in other human or yeast PATs.…”
mentioning
confidence: 99%
“…Outside of this domain, two other short motifs, TTXE and DPG, are also highly conserved (4). Finally, the palmitoyltransferase conserved C-terminal (PaCCT) motif is present in most PATs (7).…”
mentioning
confidence: 99%
“…Additionally, a diminished function of yeast Pfa3 was observed when PaCCT phenyloalanine 250 was mutated to alanine. 20 Conserved structural motifs are shown in Figure 2.…”
Section: Dhhc Proteins: Structurementioning
confidence: 99%
“…19 Most DHHC enzymes also contain a Cterminal palmitoyltransferase conserved C-terminus (PaCCT) motif (Figure 1). 20 The mutation of tyrosine 323 that is located within PaCCT results in the lack of Swf1 palmitoylation activity in vivo. Additionally, a diminished function of yeast Pfa3 was observed when PaCCT phenyloalanine 250 was mutated to alanine.…”
Section: Dhhc Proteins: Structurementioning
confidence: 99%